Spørsmål om tid og sted: Mulighetsrom og kvalifiseringsbaner blant ungdom utenfor videregående opplæring i Finnmark - Lødding, Berit; Paulgaard, Gry (Nordic Journal of Comparative and International Education (NJCIE), 2019)
Based on individual interviews with young people in Finnmark who have quit or taken a break from upper secondary education, this article addresses the relationship between attachment to place and perception of time. Finnmark is the largest and least populated county in Norway, located in the far North, with only 10 upper secondary schools. The article’s theoretical basis is a criticism of two different forms of universalisms: i) the metrocentrism in youth research and ii) normative deadlines for completion of education. As globalisation creates inequalities and changes in access to work, the article argues that it is important to examine how such changes affect young people’s perspectives and opportunities in different places. Access to localized capital, i.e. networks, embodied knowledge and reputation, can be a differentiating factor for young people’s job opportunities and lack thereof. When norms for rapid completion of education that apply to university-oriented career paths are generalized, the existence of alternative learning arenas and qualification trajectories are overlooked. Sensitivity to the young people’s material and embodied experiences, enables a richer analysis of how young people need to handle conflicting logics between attachment to place and completion of formal education elsewhere.